2016
DOI: 10.1111/nph.13995
|View full text |Cite
|
Sign up to set email alerts
|

Are trees able to grow in periods of stem shrinkage?

Abstract: SummarySeparating continuously measured stem radius (SR) fluctuations into growth-induced irreversible stem expansion (GRO) and tree water deficit-induced reversible stem shrinkage (TWD) requires a conceptualization of potential growth processes that may occur during periods of shrinking and expanding SR below a precedent maximum. Here, we investigated two physiological concepts: the linear growth (LG) concept, assuming linear growth, versus the zero growth (ZG) concept, assuming no growth during periods of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
206
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(244 citation statements)
references
References 59 publications
(129 reference statements)
3
206
0
1
Order By: Relevance
“…SDV were also used to calculate the daily radial increment for all 24 trees. We considered growth to only occur during periods of effective diameter increases, and assumed no growth during periods of stem shrinkage (Zweifel, Haeni, Buchmann, & Eugster, ). Hence, during times of radial shrinkage, stem diameter was set to the last maximum measured before shrinkage for the calculation of daily increment growth.…”
Section: Methodsmentioning
confidence: 99%
“…SDV were also used to calculate the daily radial increment for all 24 trees. We considered growth to only occur during periods of effective diameter increases, and assumed no growth during periods of stem shrinkage (Zweifel, Haeni, Buchmann, & Eugster, ). Hence, during times of radial shrinkage, stem diameter was set to the last maximum measured before shrinkage for the calculation of daily increment growth.…”
Section: Methodsmentioning
confidence: 99%
“…However, empirical studies have shown that the correlation between photosynthetic production and the diameter growth of trees is far from perfect Rocha et al, 2006;Berninger et al, 2004). This imperfect correlation is due to the fact that plant hydraulics (e.g., turgor pressure) and thermal limitations during very short periods of time can be more important than carbon (C) availability for secondary tree growth (Kirdyanov et al, 2003;Rossi et al, 2016;Zweifel et al, 2016;Fatichi et al, 2014; secondary growth is the increase in the girth of the plant roots and stems). These factors influence the proportion of net primary productivity allocated to stem growth each year, dampening the correlation between gross primary production (GPP) and growth.…”
Section: Introductionmentioning
confidence: 99%
“…Dendrometer data of stem radial changes include water content variability and growth; therefore, stem radial changes of each tree were detrended for growth based on the zero-growth concept as described in Zweifel [23] (Figure 1a,b), and used to indicate drought stress in trees [21,43]. Tree water deficit (∆W) was calculated as the difference between the past highest stem radial record (SRmax) and current stem radial reading (SRt) when SRt < SRmax, with ∆W = 0 when SRt > SRmax [24], that is, the difference between growth trend and stem radial fluctuations ( Figure 1a,b and Figure 2d). A ∆W of zero indicated an optimal water content of the cambial zone, while increasingly positive values meant increasing water stress.…”
Section: Stem Radial Change Measurements and Related Parametersmentioning
confidence: 99%
“…In early May, stem radial changes were due to spring rehydration following winter desiccation and subsequent precipitation [63][64][65]. Stem radial growth ended by late August and fluctuations in stem radial measurements were caused by tree water status [24]. Based on this, we focused on the periods from middle May to early August.…”
Section: Effects Of Environmental Variables On Water Use Efficiencymentioning
confidence: 99%
See 1 more Smart Citation